Optical PIV and LDV Comparisons of Internal Flow Investigations in SHF Impeller - G. Wuibaut; G. Bois; M. El Hajem; A. Akhras; J. Y. Champagne (International Journal of Rotating Machinery)
The paper presents a comparison between two sets of experimental results in a centrifugal flow pump. The tested impeller is the so-called SHF impeller for which many experimental data have been continuously produced to built databases for CFD code validations with various levels of approximation. Measurements have been performed using optical techniques: 2D particle image velocimetry (PIV) technique on an air test model and 2D laser doppler velocimetry (LDV) technique on a water model, both for different flow rates. For the present study, results obtained by these optical techniques are compared together in terms of phase averaged velocity and velocity fluctuations inside the impeller flow passage for design flow rate.